TEOSOFI MAHABBAH DAN PARA TOKOH MAHHABBAH MENURUT AL-QUR’AN DAN HADIST - Shofil Fikri; Dinda Novrika Fitria Yusup (Tarbawi, 2022)
Mahabbah or love is a science that emphasizes feelings of love for God. When someone wants to achieve ma'rifat to Allah, then one will go through this stage. Mahabbah is basically a gift that forms the basis for everything. The Quran explains that the feeling of love is stronger than anything else except Allah. Islam recognizes the presence of love that is implanted in every human heart, as a gift, with that feeling one will love their partner, family, wealth, and place of residence. However, Islam does not justify that feeling of love to be stronger than the love for Allah as the Creator. This study aims to determine the urgency of mahabbah, getting closer to Allah, and to understand the history of the development of mahabbah. The modern era brings many problems in human life, ranging from social crises, structural crises to moral crises, because humans are less able to see the true meaning of life. Material wealth is considered as the actualization of life. Therefore, it is important to emphasize mahabbah in each individual, because by cultivating love for Allah, Allah will pour out His mercy so that we can avoid actions prohibited by Allah SWT.